Effects and mechanisms of tapering in maximizing muscular strength - Prichard, H.; Keogh, J.; Barnes, M.; McGuigan, M. (Strength and Conditioning Journal, 2015)
Tapering for maximal strength requires reductions in training load to recover from the fatigue of training. It is performed before important competitions to allow optimal performance at specific events. Reductions in training volume, with maintained or small increases in training intensity, seem most effective for improving muscular strength. Training cessation may also play a role, with less than 1 week being optimal for performance maintenance, and 2-4 days appearing to be optimal for enhanced maximal muscular strength. Improved performance may be related to more complete muscle recovery, greater neural activation, and an enhanced anabolic environment.